Cisplatin and Pemetrexed Activate AXL and AXL Inhibitor BGB324 Enhances Mesothelioma Cell Death from Chemotherapy - Oien, Derek B.; Garay, Tamás; Eckstein, Sarah; Chien, Jeremy (Frontiers in Pharmacology, 2018)
Reactive oxygen species (ROS) can promote or inhibit tumorigenesis. In mesothelioma, asbestos exposure to serous membranes induces ROS through iron content and chronic inflammation, and ROS promote cell survival signaling in mesothelioma. Moreover, a current chemotherapy regimen for mesothelioma consisting of a platinum and antifolate agent combination also induce ROS. Mesothelioma is notoriously chemotherapy-resistant, and we propose that ROS induced by cisplatin and pemetrexed may promote cell survival signaling pathways, which ultimately may contribute to chemotherapy resistance. In The Cancer Genome Atlas datasets, we found AXL kinase expression is relatively high in mesothelioma compared to other cancer samples. We showed that ROS induce the phosphorylation of AXL, which was blocked by the selective inhibitor BGB324 in VMC40 and P31 mesothelioma cells. We also showed that cisplatin and pemetrexed induce the phosphorylation of AXL and Akt, which was also blocked by BGB324 as well as by N-acetylcysteine antioxidant. AXL knockdown in these cells enhances sensitivity to cisplatin and pemetrexed. Similarly, AXL inhibitor BGB324 also enhances sensitivity to cisplatin and pemetrexed. Finally, higher synergy was observed when cells were pretreated with BGB324 before adding chemotherapy. These results demonstrate cisplatin and pemetrexed induce ROS that activate AXL, and blocking AXL activation enhances the efficacy of cisplatin and pemetrexed. These results suggest AXL inhibition combined with the current chemotherapy regimen may represent an effective strategy to enhance the efficacy of chemotherapy in mesothelioma. This is the first study, to our knowledge, on chemotherapy-induced activation of AXL and cell survival pathways associated with ROS signaling.